Psychiatric Aspect of Infanticide and Filicide in the Context of a Case - Savaş, Haluk; Çakıcı, Mehmet; Uygur, Niyazi (The Bulletin of Legal Medicine, 1999)
The act of killing one’s own child can be done with many and heterogenous motivations. Especially mothers attitudes for killing their children, although had always been interpreted as a psychotic behaviour, nowadays is thought as an act that can be done with different motivations. Psychotic mothers generally kill their children with a feeling that can be called as "pity" (mercy killing). But there are also other infanticides which has different motivations than "pity" and done with an impulsive psychotic behavior. This article is about a mother with a diagnosis of psychotic depression who killed her five days old child and had previously killed her other child of nine years old eight years ago. This case is discussed within the context of infanticides and filicides in the literature with its features of being a result of impulsive psychotic behaviour which is a rare motivation of infanticide and filicide and of having recurrent occurence. Key words: Filicide, infanticide, motivation